Magento PHP developer's guide get up and running with the highly customizable and powerful e-commerce solution, Magento - MacGregor, Allan (Packt Publishing, 2015)
This book is written for PHP developers who are familiar with frameworks such as Zend or CakePHP and want to start developing and working with Magento. No prior knowledge of Magento is required.
Includes index. - Online resource; title from cover (Safari, viewed August 11, 2015)
Keywords: PHP (Computer program language); Electronic commerce -- Computer programs; Computer software -- Development; PHP (Langage de programmation); Commerce électronique; Logiciels; COMPUTERS; Web; Content Management Systems; COMPUTERS; Internet; Application Development; Computer software; Development; Electronic commerce; Computer programs